ANALYSIS KEANDALAN UNTUK MENINGKATKAN EFEKTIVITAS PENGGUNAAN FORKLIFT DENGAN METODE RELIABILITY ANALYSIS DAN MACHINE’S EFFECTIVENESS - M. Kastalani; Mochammad Basjir; Cepi Yazirin; Nur Robbi (Journal of Research and Technology, 2023)
Abstract Production machine maintenance is an activity to maintain the machine's reliability to operate as planned. Apart from reliability, evaluating the effectiveness of the machine is also equally important. Therefore, this research has two main objectives: determining the system's criticality and increasing the effectiveness value of using forklifts using reliability analysis and machine's effectiveness (ME). The research began with collecting operation and maintenance data to calculate the initial conditions of machine reliability and effectiveness. The initial reliability calculation results were 36.79%. Availability is 98.89%, performance is 93.53%, and ME value is 92.49%. The performance value is still below world-class standards, so it needs to be improved. Next, rank the problem using the Pareto diagram for determining system criticality. Efforts to increase performance values to reach world-class standards are carried out by analyzing maintainability and implementing a policy that maintainability values are at least 50% for forklifts and their critical systems. As a result, the availability value increased to 99.74%, the performance value increased to 95.57%, and the ME value increased to 95.32%. So availability, performance, and ME meet the requirements because they exceed world-class standards. Therefore, companies can implement a forklift maintenance policy using maintainability of at least 50% reliability to increase the value of availability, performance, and ME. Keywords: Forklift, Reliability Analysis, Machine’s Effectiveness, Maintainability